2016
DOI: 10.1021/acschemneuro.6b00024
|View full text |Cite
|
Sign up to set email alerts
|

An ex Vivo Model for Evaluating Blood–Brain Barrier Permeability, Efflux, and Drug Metabolism

Abstract: The metabolism of drugs in the brain is difficult to study in most species because of enzymatic instability in vitro and interference from peripheral metabolism in vivo. A locust ex vivo model that combines brain barrier penetration, efflux, metabolism, and analysis of the unbound fraction in intact brains was evaluated using known drugs. Clozapine was analyzed, and its major metabolites, clozapine N-oxide (CNO) and N-desmethylclozapine (NDMC), were identified and quantified. The back-transformation of CNO int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Collectively, these data indicate that CNO is a substrate for Pgp-mediated efflux at the BBB in vitro . Our results are in agreement with previous studies demonstrating low blood–brain permeability of CNO 19 and may account for its limited CNS distribution (i.e., exposure) in vivo in NHP.…”
Section: Resultssupporting
confidence: 93%
“…Collectively, these data indicate that CNO is a substrate for Pgp-mediated efflux at the BBB in vitro . Our results are in agreement with previous studies demonstrating low blood–brain permeability of CNO 19 and may account for its limited CNS distribution (i.e., exposure) in vivo in NHP.…”
Section: Resultssupporting
confidence: 93%
“…The major argument resides in the fact that the radiolabeled CNO signal could have been due to converted radiolabeled clozapine. Indeed, contrasting results from clozapine/CNO plasma measurements were reported in rodents and in monkeys detecting clozapine after CNO systemic injections (Hellman et al 2016;Gomez et al 2017;Raper et al 2017) or not (Alexander et al 2009;Guettier et al 2009;Nagai et al 2016). It still remains elusive to explain or reconcile these differences.…”
Section: 3mentioning
confidence: 94%
“…From many reports, CNO appeared to be pharmacologically and behaviorally inert in rodents (Bender et al 1994;Armbruster et al 2007;Alexander et al 2009;Guettier et al 2009). However, recent studies performed in mice, rats, and monkeys further investigated this possibility by measuring the presence of clozapine following CNO administration through various assays (Hellman et al 2016;Gomez et al 2017;Raper et al 2017). Additionally, the blood-brain permeability of CNO has been reexamined (Hellman et al 2016;Ji et al 2016;Nagai et al 2016;Gomez et al 2017;Raper et al 2017).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the metabolic capacity of the BBB, recent studies have shifted attention to investigating phase I and phase II metabolism at the site of the barrier. To assess cytochrome P450 metabolism, Hellman et al () utilized an ex vivo locust model to investigate local phase I metabolic rates of selected pharmaceuticals at the site of the BBB (Hellman, Aadal Nielsen, Ek, & Olsson, ). While this invertebrate model does not have an endothelial cell based physical barrier, the authors demonstrated CYP activity through xenobiotic metabolism.…”
Section: Bbb Formationmentioning
confidence: 99%